A rare ovarian Leydig cell tumour masquerading as postmenopausal bleeding: a case report - Joy, Kiran; Mathew, Susan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian Sertoli-Leydig cell tumors (SLCTs) are rare ones, accounting for less than 0.2% of ovarian malignancies. While typically associated with virilization, they can present atypically with postmenopausal bleeding. We report a 72-year-old postmenopausal woman with post-menopausal bleeding. The diagnosis was endometrial hyperplasia. The patient, with a history of diabetes, hypertension, and dyslipidemia, had postmenopausal bleeding lasting five days without features of virilization. Ultrasonography showed a bulky uterus with a fibroid, adenomyoma, and thickened endometrium. Endometrial sampling revealed focal hyperplasia without atypia. Despite progestin therapy, she had recurrent vaginal bleeding. Hence decision for surgical management was sought. Histopathology confirmed a 1 cm Leydig cell tumour in the right ovary, with no significant findings in the left ovary or tubes.